2019
DOI: 10.1177/0300060519874159
|View full text |Cite
|
Sign up to set email alerts
|

Value of contrast-enhanced ultrasound for detection of synovial vascularity in experimental rheumatoid arthritis: an exploratory study

Abstract: ObjectiveThis study aimed to examine the associations between contrast-enhanced ultrasound (CEUS) imaging and synovial hypervascularity and synovitis score in a rabbit model of antigen-induced arthritis (AIA), compared with power Doppler ultrasound (PDUS).MethodsWe investigated 50 knee joints in 25 AIA rabbits (AIA group), and 10 knee joints in five sham-injected rabbits (control group). PDUS and CEUS images were evaluated at the 8th week. Ultrasound-guided synovial biopsies were targeted in the area with hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
0
5
1
1
Order By: Relevance
“…Although ultrasound imaging of the joint synovium is more complex due to the presence of surrounding articulate bones (i.e., femur and tibia in the knee joint) (Figure 2B), the synovial cavity and synovial microbubble influx could be clearly visualized (Figure 2D). However, we could not detect any differences in the maximal contrast enhancement and time to peak of the contrast-enhanced ultrasound signal between healthy and inflamed synovia, which differs from results obtained in humans [12,[71][72][73]. A possible explanation for this discrepancy may lie in the difference in microvasculature size between humans and mice.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Although ultrasound imaging of the joint synovium is more complex due to the presence of surrounding articulate bones (i.e., femur and tibia in the knee joint) (Figure 2B), the synovial cavity and synovial microbubble influx could be clearly visualized (Figure 2D). However, we could not detect any differences in the maximal contrast enhancement and time to peak of the contrast-enhanced ultrasound signal between healthy and inflamed synovia, which differs from results obtained in humans [12,[71][72][73]. A possible explanation for this discrepancy may lie in the difference in microvasculature size between humans and mice.…”
Section: Discussioncontrasting
confidence: 99%
“…A possible explanation for this discrepancy may lie in the difference in microvasculature size between humans and mice. Whereas the microvasculature in human knee joints (d = 11 µm) [104] is known to be large enough to permit CEUS imaging with micron-sized microbubbles [12,71,73], Raatz et al determined that the murine neo-vasculature in CIA knee synovia is about 2-times smaller (d = 5.8 µm), which may already hamper efficient microbubble perfusion [81]. In addition, Raatz et al found that the functionality of the synovial vasculature is significantly decreased [81,105,106].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional information during US imaging can be obtained through sonoelastography and contrast-enhanced ultrasonography (CEUS) [11][12][13][14][15]. These two US techniques have been studied and proven their usefulness in certain rheumatic diseases, but nevertheless, they are not so widely used as conventional gray scale (GS) and Doppler modalities.…”
Section: Principles Of Ultrasound Examination In Rheumatologymentioning
confidence: 99%
“…CEUS can assess joint inflammation and provides a view of the exact vascular patterns, which can also be visible in inflamed sacroiliac joints [10,18]. Some studies report the superiority of CEUS compared to power Doppler US in detecting synovial hypervascularity [14,15]. Compared to the known risks of using contrast agents in MRI and CT, contrast agents used in CEUS have no proof of significant side-effects.…”
Section: Principles Of Ultrasound Examination In Rheumatologymentioning
confidence: 99%